Alih Fungsi Lahan Persawahan Menjadi Perumahan di Kabupaten Jember Berdasarkan Peraturan Daerah Kabupaten Jember Nomor 1 Tahun 2015 Tentang Rencana Tata Ruang Wilayah Kabupaten Jember Tahun 2015-2035 - Santoso, M. Iqbal Sun’an; Fitri, Icha Cahyaning (Journal of Contemporary Law Studies, 2023)
Indonesia as an agricultural country is a country rich in agriculture. Land is a very important part of everyday life, the main function of land is as a place to live, apart from that land can be used for plantations, industry and many other uses such as social functions. As settlements become increasingly dense and more land is converted into housing and settlements, the amount of land is decreasing, the problems arising from land conversion activities are very worrying, so this case is very concerning. This research uses a statutory and conceptual approach with a normative juridical research type. The conversion of rice fields into housing in Jember Regency is based on Jember Regency Regional Regulation Number 1 of 2015 concerning Jember Regency Spatial Planning for 2015-2035. Jember Regency is one of the administrative regions of East Java Province. Most of the Jember Regency area is lowland, with an average land height of 83 meters above sea level and is an area that is quite fertile and very suitable for the development of agricultural commodities and plantations, so it is known as an area or food barn and a country's foreign exchange earner in the agricultural sector. East Java Province. However, agricultural land in Jember Regency has experienced many changes, characterized by increasingly narrow agricultural land. The narrowing of agricultural land in Jember Regency is due to housing construction which is increasing every year. The conversion of land in agricultural areas not only results in rice yields, but many other productions have to be sacrificed.